Greening Australia collection - Fox, Allan, 1931-2013. ([Australia] : Greening Australia, 1990)
Features a photograph of a wetland surrounded by trees with a large rock formation visible in the distance.
"Nourlangie Rock, Kakadu National Park".
Catalogue record generated as part of a batch load.
Also available online
Keywords: Fox, Allan, -- 1931-2013 -- Posters; Greening Australia (Organization) -- Posters; Kakadu National Park (N.T.) -- Posters